Aircraft performance - Saarlas, Maido (John Wiley, 2007)
Aircraft Performance sets forth a group of tested and proven methods needed to determine the performance of an aircraft. The central theme of this book is the energy method, which enhances understanding of the standard methods and provides accessibility to advanced topics. As a result, readers gain a thorough understanding of the performance issues involved in operating an aircraft in an efficient and economic manner.